BENTUK PENYAJIAN TARI PERSEMBAHAN MELAYU DI KOTA RANAI KABUPATEN NATUNA KEPULAUAN RIAU - Sephia, Nur Malika; Ismunandar, Ismunandar; Aditya, Mega Cantik Putri (Universitas Tanjungpura, 2023)
This study aims to describe and document the form of the presentation of Persembahan Dance in Ranai City, Natuna Regency, Riau Archipelago in the form of writing, pictures, and videos. The background of the research is the problem of how the form of Persembahan Melayu Dance. This study used descriptive method with qualitative research and choreographic approach. The technique of data collection used in this research are observation techniques, interview techniques, and documentation studies. The data validation testing used are the extension of observations and triangulation source. Based on the data analysis, it can be concluded that the form of Persembahan Melayu Dance is as follows: Persembahan Melayu Dance is a welcoming dance for guests of honor or opening dance at various events. There are 11 movements of Persembahan Melayu Dance which are initial movement, the variety of junjung tepak to the variety of opening greeting, the middle movement, the variety of meracik pinang to the variety of sari beni, and the final movement, the variety of close greeting. This dance is only danced by the female dancer and it must be an odd number, also there are six floor patterns. Musical instruments used are drum, violin, accordion, and it do not use vocal. The make-up used is realist make-up. The make-up used is realist make-up, the clothes used are clothes for brackets, skirts, tapeh cloth, obi, sebai and use andam head accessories, crowns, Malay editing, jurai, tudung mantu, and bun. Also, this dance uses tepak sirih as the property.